Perbedaan Tingkat Stres antara Mahasiswa yang Merokok dengan Mahasiswa yang Tidak Merokok Saat Mengerjakan Skripsi - Muhammad Althaf Novandri; Amin Akbar (Indo Publishing, 2026)
This study aims to determine the differences in stress levels between students who smoke and students who do not smoke when working on their theses at the undergraduate program (S1) of Padang State University. This study uses purposive sampling techniques with a sample of 389 respondents. Based on the results of the study, it can be confirmed that there are significant differences in stress levels between students who smoke and students who do not smoke in working on their theses. Students who smoke consistently show higher stress levels than non-smokers. This confirms that smoking behavior is significantly associated with increased levels of perceived stress in the face of academic challenges. These findings support Lazarus and Folkman's transactional stress theory, which emphasizes the role of cognitive appraisal and coping strategies in understanding individual stress responses. Furthermore, the results of this study clearly support Cohen's perception-of-stress concept, which states that stress is influenced by an individual's perception of control and situational pressure. Therefore, non-smoking students have a more adaptive perception of control, resulting in lower levels of stress than smokers.